Capturing biologic treatment for IBD in the Swedish Prescribed Drug Register and the Swedish National Patient Register – a validation study. (3rd April 2021) - Bröms, Gabriella; Söderling, Jonas; Sachs, Michael C.; Halfvarson, Jonas; Myrelid, Par; Ludvigsson, Jonas F.; Everhov, Åsa H.; Olén, Ola
Abstract: Background: It is not known to what extent biologic treatment for IBD is captured in the Swedish Prescribed Drug Register (PDR) and the National Patient Register (NPR). Methods: A cross-sectional study from July 2005 until 2017, comparing data on biologic treatment in the PDR and the NPR with medical records. We assessed the proportion of started treatment episodes in the medical records that were found in the PDR/NPR ever, within +/− one year and within +/− three months; for any biologic drug, per specific drug (infliximab, adalimumab, golimumab, vedolizumab, ustekinumab), by calendar period (2005–2008, 2009–2012, and 2013–2017) and by study center. For adalimumab, we assessed the validity of end of treatment episodes. Results: Medical records of 1361 patients and 2323 treatment episodes with any biologic were reviewed and 80.1% (95% CI: 78.4–81.7) were ever captured in the PDR/NPR in. A time window of +/− one year or +/− three months reduced the sensitivity to 63.3% (95% CI: 61.3–65.3) and 52.6% (95% CI: 50.5–54.6), respectively. The sensitivity was high (>85%) for the prescribed injection drugs adalimumab, golimumab, and ustekinumab for all time windows and for adalimumab end of treatment, while considerably lower for the infusion drugs infliximab and vedolizumab. Conclusions: The PDR and the NPR are reliable data sources on treatment with injection biologics in patients with IBD in Sweden. Infliximab and vedolizumab are poorly captured, why PDR/NPR data should only be used after careful consideration of their limitations or complemented by other data sources, e.g., the disease-specific quality register SWIBREG.